Acute organ toxicity correlates with better clinical outcome after chemoradiotherapy in patients with anal carcinoma. (August 2020) - Martin, Daniel; Rödel, Franz; von der Grün, Jens; Rödel, Claus; Fokas, Emmanouil
Highlights: Organ toxicity during treatment of anal cancer was associated with improved disease-free survival. Organ toxicity was independent of tumor stage, gender and HIV status. These data suggest an interrelationship between normal organ and cancer cell chemoradiosensitivity. Abstract: Background and purpose: Previous studies have shown that acute organ toxicity to (chemo)radiotherapy (CRT) is associated with improved oncological outcome in various tumor types. The aim of the present study was to investigate the relationship of toxicity with clinical outcome in a large cohort of 223 patients with anal squamous cell carcinoma (ASCC) treated with standard CRT. Materials and methods: We identified 223 patients treated with definitive CRT for non-metastasized ASCC. Acute organ toxicities were scored weekly as part of the clinical routine. Dermatitis, diarrhea, proctitis and cystitis of ≥ grade 3 was defined as a high-grade acute organ toxicity (HGAOT). High-grade acute hematologic toxicity (HGAHT) defined as a hematologic toxicity ≥ grade 3 was assessed as well. Results: In total 107 (48%) patients experienced at least one HGAOT during CRT with the most common being dermatitis (40% ≥ grade 3). No correlation of HGAOT was noted with either tumor stage, gender, or radiotherapy technique. With a median-follow-up of 46 months, patients with HGAOT had significantly better disease-free survival (DFS, p  = 0.008). In contrast, HGAHT did not impact DFS ( p  = 0.30). Multivariate analysis revealed that HGAOT was an independent prognostic factor for DFS (HR 0.47 95% CI: 0.27–0.83, p  = 0.01) in addition to N-stage (HR 3.06 95% CI: 1.70–5.49, p  < 0.001) and gender (HR 0.47 95% CI: 0.26–0.84, p  = 0.01). Conclusion: To the best of our knowledge, this is the largest study in ASCC to demonstrate the association of HGAOT with better oncological outcome after standard CRT. Further studies are needed to elucidate the possible underlying mechanisms behind this intriguing clinical phenomenon.